Neutrophil-to-lymphocyte ratio predicts 30-, 90-, and 180-day readmissions of patients with hepatic encephalopathy - Zhang, Lin; Zhang, Wei; Wang, Jian; Jin, Qian; Ma, Danli; Huang, Rui (Frontiers in Medicine, 2023)
Introduction: Hepatic encephalopathy (HE) is a significant complication of cirrhosis, known to be associated with hospital readmission. However, few new serological indicators associated with readmission in HE patients have been identified and reported. The objective of our study was to identify simple and effective predictors related to readmission in HE patients. Materials and Methods: We conducted a retrospective study at a single center on adult patients admitted with HE from January 2018 to December 2022. The primary endpoint was the first liver-related readmission within 30, 90, and 180 days, and we collected electronic medical records from our hospital for sociodemographic, clinical, and hospitalization characteristics. We utilized logistic regression analysis and multiple linear regression analysis to determine the predictors that were associated with the readmission rate and length of the first hospitalization. Results: A total of 424 patients were included in the study, among whom 24 (5.7%), 63 (14.8%), and 92 (21.7%) were readmitted within 30, 90, and 180 days, respectively. Logistic regression analysis showed that insurance status, alcoholic liver disease (ALD), ascites, model for end-stage liver disease (MELD) score, and neutrophil-to-lymphocyte ratio (NLR) were significantly associated with 30-, 90- and 180-day readmissions. Age and hepatocellular carcinoma (HCC) were predictors of 90- and 180-day readmission. ALD was identified as a unique predictor of readmission in males, while hypertension was a predictor of 180-day readmission in females. Variceal bleeding, chronic kidney disease, and MELD score were associated with the length of the first hospitalization. Conclusions: NLR at discharge was identified as a significant predictor of 30-, 90- and 180-day readmission in patients with HE. Our findings suggest that incorporating NLR into routine clinical assessments could improve the evaluation of prognosis of liver cirrhosis.